2016
DOI: 10.1016/j.scitotenv.2016.01.085
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nanomaterials on marine invertebrates

Abstract: The development of nanotechnology will inevitably lead to the release of consistent amounts of nanomaterials (NMs) and nanoparticles (NPs) into marine ecosystems. Ecotoxicological studies have been carried out to identify potential biological targets of NPs, and suitable models for predicting their impact on the health of the marine environment. Recent studies in invertebrates mainly focused on NP accumulation and sub-lethal effects, rather than acute toxicity. Among marine invertebrates, bivalves represent by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
99
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(106 citation statements)
references
References 88 publications
2
99
0
5
Order By: Relevance
“…As a result, predicted environmental concentrations for AgNP are often set at a level of % 0.01 lg/L (Tiede et al 2009;Katsumiti et al 2015). Even so, levels much lower than that have commonly been used in aquatic species ecotoxicity tests (1-100 lg/L) (Tiede et al 2009;Canesi & Corsi 2016), including those with mollusk models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, predicted environmental concentrations for AgNP are often set at a level of % 0.01 lg/L (Tiede et al 2009;Katsumiti et al 2015). Even so, levels much lower than that have commonly been used in aquatic species ecotoxicity tests (1-100 lg/L) (Tiede et al 2009;Canesi & Corsi 2016), including those with mollusk models.…”
Section: Introductionmentioning
confidence: 99%
“…Internalization of these NP subsequently impacted on morphologic/functional characteristics including immune responses (Canesi et al 2008(Canesi et al , 2010a(Canesi et al , b, 2012Katsumiti et al 2015;Marisa et al 2016). Various mussel hemocyte parameters, including total hemocyte count (THC), differential hemocyte count (DHC), hemocyte viability, phagocytic activity and lysosomal membrane stability, have been used as a tool for screening of immunomodulatory effects of differing NP (Matozzo et al 2007;Parisi et al 2008;Hoher et al 2013;Matozzo & Bailo 2015;Canesi & Corsi, 2016;Marisa et al 2016). Specifically, hyalinocytes and granulocytes have been assessed for morphological changes among hemocytes in Mytilus galloprovincialis (Pipe et al 1997;Chang et al 2005;Garcia-Garcia et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…NPs have been widely applied in various areas, including the production of more than 1800 consumer products (Bour et al, 2015;Nel et al, 2006) and hence they inevitably enter the aquatic environment (Hall et al, 2009;Menard et al, 2011). In recent years, the toxicity and safety of NPs have become closely reviewed issues in the field of ecotoxicology, but toxic mechanisms of various NPs have not been understood comprehensively to date (Canesi and Corsi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of toxicological researches have reported the toxic effects of NPs on marine invertebrates (Jiang et al, 2008;Canesi and Corsi, 2016). For example, Canesi et al (2010) found that nanoscale titanium dioxide (nano-TiO 2 ) induced toxic effects on the mussel M. galloprovincialis at 1-10 mg L −1 concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation